Optimalisasi PenyelesaianSengketa Kewenangan Antar Lembaga Negaraoleh Mahkamah Konstitusi - Mochammad Hilmi Alfarisi, Hilmi (Jurnal Panorama Hukum, 2020)
State institutions are divided into two, namely, first, the core state institutions or central state institutions and two, supporting state institutions or auxiliary organs based on the provisions of Article 24C paragraph (1) of the 1945 Constitution of the Republic of Indonesia and Article 10 Paragraph (1) of the Constitutional Court Law, requests for disputes over the authority of state institutions can only be made if 2 (two) conditions are fulfilled. The two conditions are: 1) the applicant is a state institution referred to in the 1945 Constitution; and 2) the disputed authority is the authority granted by the Basic Law. The dictation of "disputes over the authority of state institutions whose authority is given by the Basic Law" also means that only the authority granted by the Constitution is the object of a dispute over the authority of state institutions by the Constitutional Court.